An evaluation of the provision of terminal facilities for the design of low cost airport terminals - Sabar, Rohafiz (Cranfield University, 2009)
The growth of the Low Cost Carriers (LCCs) in the world will have a significant impact on future airport development. LCCs such as Ryanair, Air Asia and EasyJet prefer only basic terminal facilities (TFs) at Low Cost Terminals (LCTs) to reduce associated costs (airport charges, capital investment, operational costs). Pressure by LCCs for reduced airport charges has led to the inclusion of only basic TFs so as to reduce capital investment and operational costs. This has raised an interest in the evaluation of TFs within LCT design. A reduction of airport charges, which is possible through LCTs, is indirectly linked to the reduction in air fares. The debate concerning the development of the ‘right’ TFs has led to considerable discussion by airport operators. Airports have to retain the airlines as business partners and customers. To this end, they need to develop facilities that offer best value in order to retain their custom. In addition, airports must be flexible enough to meet the changing needs of passengers. With particular emphasis on experiences at Kuala Lumpur International Airport (KLIA), this research is an evaluation the provision of TFs for a LCT model, taking into account potentially conflicting expectations of airline and airport managements, and passengers. A research framework was developed as the result of a literature review of LCT design and development. The research itself used multiple questionnaires in pre- and postdevelopment surveys involving three different parties: airline management (Air Asia Berhad), airport operator (Malaysia Airports Holding Berhad) and passengers (LCT users). The headquarters of Air Asia Berhad and Malaysia Airports Berhad were visited and surveys were undertaken to ascertain the viewpoints of LCC passengers flying with Air Asia, a low-cost airline based at KLIA, Malaysia. The main focus of this research has been to propose a possible conceptual model for LCT design with an emphasis on simplifying the provision of TFs in such a way as to reduce capital investment and operational and airport charges, while at the same time being able to generate additional airport revenues. The evidence from the surveys reveals that, in LCT design, there are conflicting expectations between airlines, airport authorities and passengers on the adequacy of TFs whose design is influenced by consideration of cost and revenue structures. The proposed conceptual model indicates the preferences for core and secondary TFs within LCT design after the cost and revenue structures, and airline management, airport operator and passenger’s expectations, are considered.